PENGARUH PENGGUNAAN MORDAN JERUK LEMON (CITRUS LIMON ) DAN ARANG SEBAGAI ADSORBEN TERHADAP HASIL WARNA DAUN PACAR (LAWSONIA INERMIS) - Rahma Nizer (JURNAL PENDIDIKAN DAN KELUARGA, 2019)
Henna leaves (lawsonia inermis) is one of the natural ingredients used to color the skin. It is used as a natural coloring skin which is not used because people tend to choose instant henna. To optimize the use of henna leaves, the author uses mordan lemon and charcoal adsorbent as a generator for the color of henna leaves. This study aims to see the effect of the use of lemon mordan and charcoal adsorbent toward the result of henna leaves color. This research is using experimental method. The subject of the study is the hand’s skin called palm where the samples were taken from 3 students who were treated by 3 different henna leaves. The result showed that, obtained colors (hue) produced on the coloring of the skin using the leaves of a boyfriend without mordan namely 4 panelists or 66.67% stated apricots, 1 panelist or 16.67% stated Carrot and 1 panelist or 16.67 % declares Ocher. The color of the henna leaves without using mordans, namely apricot orange. The results of the panelist's assessment of coloring using the henna leaves with lemon mordan 5 panelists or 83.33% stated Squash, 1 panelist or 16.67% stated Ginger and the direction of the resulting color is dark orange. While the color result of using henna leaves with lemon mordans and charcoal adsorbent 6 panelists or 100% declared Bronze, color direction resulted was copper orange. It proves that there is an effect of using lemon mordan and charcoal adsorbent on skin coloring using henna leaves. Based on the normality testing that has been done, it is obtained that the data is normally distributed. The homogeneity testing that has been done is obtained that the three data have the same variant (homogeneous). Based on the ANOVA test obtained Fcount of 4.375, while the value of Ftable is 3.34. thus Fcount> Ftable (4.375> 3.34) this proves that the hypothesis that reads there is no difference in the results of dark bright colors (value) on skin coloring using henna leaves without the use of mordan, using mordan lemon, and mordan lemon (citrun) with charcoal adsorbent rejected. For further research it is recommended to examine the effect of using mordan alum on the results of henna leaf color. Keywords: henna, mordant , adsorben